Connaissances des Prescripteurs en Radioprotection des Patients en Centrafrique - Francky, Kouandongui Bangue Songrou; Henri, Diemer; Euloge, Bidan Tapiade; Moise, Ouimon; Timothée, Mobima (European Scientific Journal, ESJ, 2019)
The aim of this study was to assess the level of knowledge of X-ray examination prescribers before the advent of CT in Central Africa Republic. It was a descriptive study from October to December 2018 among radiology prescribers of the internal medicine and emergency departments of the Bangui Hospital and University Centers. The material used consisted of individual questionnaire cards. Each answer to just one question was scored as 1 point. An overall knowledge score of less than 10 points was rated worse; between 10 and 11, it was classified average; between 12 and 13; he was ranked fairly well and between 14 and 16 he was ranked very well. Out of a total of 85 practitioners, 68 responded to the questionnaires. The average age was 39 years (± 10), men accounted for 72%, 26.5% of the practitioners were State Graduate Nurses (FDI), 33.8% were general practitioners, 16.1% were health assistants (AS) and 11.8% were medical specialists and students in the last year of medical training. The overall average knowledge score varies by staff profile. No statistically significant relationship was observed between the level of radiation protection knowledge ofstaff. Almost all of the respondents (97%) said they wanted to participate in radiation protection training for the patient. The training of radiographic examination prescribers is essential, and a guide to the correct use of medical imaging examinations must also be made available to them. Le but de l’étude était d’évaluer le niveau de connaissance des prescripteurs d’examens radiographiques en Centrafrique avant l’avènement du scanner. C’était une étude descriptive réalisée entre Octobre et Décembre 2018 sousforme d’enquête auprès des prescripteurs de radiologie desservices de médecine interne et des urgences des Centres Hospitaliers et Universitaires de Bangui. Le matériel utilisé était constitué de questionnaires individuels. Chaque réponse juste à une question était notée 1 point. Un score global de connaissances inférieur à 10 points était classé moins bon ; entre 10 et 11 était classé moyen ; entre 12 et 13était classé assez bien et entre 14 et 16 était classé très bien. Sur un total de 85 praticiens, 68 ont répondu aux questionnaires. L’âge moyen était de 39ans (±10), les hommes représentaient 72%, 26,5% des praticiens étaient desInfirmiers Diplômés d’Etat (IDE), 33,8% étaient des médecins généralistes, 16,1% étaient des assistants de santé (AS) et 11,8% étaient des médecins spécialistes et des étudiants en dernière année de formation médicale. Le score global moyen des connaissances variait selon le profil du personnel sans que cela soit statistiquement significatif. La quasitotalité des enquêtés (97%) ont affirmé vouloir participer à une formation en radioprotection du patient. La formation du personnel prescripteur d’examens radiographiques est indispensable, il faut aussi mettre à leur disposition un guide du bon usage des examens d’imagerie médicale.